Autarchics Cemeteries in Joao Cabral de Melo Neto's Poems - Borsato, Fabiane Renata [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2020)
Joao Cabral de Melo Neto thematized death in many of his poems, besides the very well-known one Death and life of Severino. It is notorious the presence of poems about the individual death of artists and bullfighters; the collective death strongly connected to the individual's exploitation on the landowning society on Brazilian northeast; the conceptual death, metapoetical based, is found on the A indesejada das gentes section, in the book Agrestes. Within the context of many poems that thematize death, it is found the ones that present the cemetery image as a significant space in order to comprehend the speeches concerning the recurrent northeastern neediness. This paper intends to understand the way in which the Brazilian northeast cemiterial image is problematized and the poetical strategies employed to exhibit the cemetery and its foundation sustained on an intense social inequality. For this purpose, it is proposed to study a poetical composition mechanism based on the discussion of images, as Joao Cabral named himself and Benedito Nunes understood as a prismatic texture of composition. According to this procedure, Joao Cabral's compositive act would involve the selection and the unfolding of an image on several other forms and images, objecting an addition of perspectives, more clarity, significant concretion and depth of the language. It is hoped, after the study of the northeast cemeteries image, to base the hypothesis in which Cabral, retaking themes and images, presents a denunciative poetical project regarding the strengthening forms of the draught industry on the Brazilian northeast.
Keywords: Brazilian poetry; Joao Cabral de Melo Neto; cemeteries; discussion of images